Global Financial Stability Report, October 2012 : Summary version. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2012)
The October 2012 Global Financial Stability Report (GFSR) finds increased risks to the global financial system, with the euro area crisis the principal source of concern, and urges policymakers to act now to restore confidence, reverse capital flight, and reintegrate the euro zone. This GFSR presents a report on whether regulatory reforms are moving the financial system in the right direction, and finds that progress has been limited, partly because many reforms are in the early stages of implementation and partly because crisis intervention methods are still in use in a number of economies, delaying the movement of the financial system onto a safer path. The final chapter examines whether certain aspects of financial structure enhance economic outcomes. Indeed, some structural features are associated with better outcomes. In particular, financial buffers made up of high-quality capital and truly liquid assets tend to be associated with better economic performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet